Whole–of–society approach for influenza pandemic epicenter Containment exercise in Indonesia. Issue 7 (July 2020) - Wignjadiputro, Ira; Widaningrum, Christina; Setiawaty, Vivi; Widuri Wulandari, Endang; Sihombing, Sinurtina; Prasetyo, Wing Ardi; Azhar, Muhammad; iL Rim, Kwang; Pang Junxiong, Vincent; Waworuntu, Wiendra; Subuh, Mohammad
Abstract: Background: Since 2003, 200 cases of bird flu (H5N1) cases have been reported with 168 death (case fatality rate: 84%) in Indonesia. Pandemics are unpredictable, but the threat is imminent. Therefore, pandemic preparedness, which includes full simulation exercises, is a key to reduce this threat. Responding to the challenges, Ministry of Health (MoH) Indonesia adopted WHO pandemic risk management guideline, developed contingency plan and conducted full scale epicenter influenza pandemic simulation. Method: The exercise outlines the Government of Indonesia operational plans for Avian Influenza (AI) control from the detection of AI cases (from poultry to human transmission) and containment of human to human transmission of novel influenza virus in influenza pandemic epicenter at Setu village South Tangerang. The simulation covers multiple locations in community, hospitals, point of entry and live bird market. 25 evaluators and around 800 observers involved in the exercise. Results: The full scale pandemic epicenter containment exercise has demonstrated Indonesia capacity in whole of society approach pandemic risk management in the overall national emergency response framework, covering command and coordination, animal health response surveillance, medical response, laboratory, risk communication, perimeter control, pharmaceutical interventions, non-pharmaceutical interventions and civil-military interoperability. It is served as a momentum to improve multisector commitment on pandemic preparedness. The outcome of this exercise has contributed to identification of gaps that require further strengthening of IHR core capacities in the country to reduce the threat of the next influenza pandemic. Conclusion: There is also a critical need for more evidence-based strategies and policy formulation to strengthen pandemic preparedness.